The level of parental knowledge regarding myofunctional therapy in Down's syndrome: Study cross-sectional - Bachtiar, Rindu Wulandari; Soewondo, Willyanti; Primarti, Risti Saptarini (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACT Introduction: Down syndrome is a genetic disorder associated with the addition of chromosome 21 and is still one of the most common birth defects. One of the distinctive physical characteristics found is muscle hypotonia, including the orofacial muscles and tongue muscles. Management of muscle hypotonia must be treated with myofunctional therapy, which is carried out routinely. The purpose of this study is to obtain data on the level of parents’ knowledge regarding myofunctional therapy for Down syndrome at the Association of Parents of Children with Down Syndrome (POTADS). Methods: The type of research is a cross-sectional survey design. The purposive sampling method was used to collect samples,resulting in 96 research samples from POTADS. Data collection was carried out using a questionnaire via the Google Form tool. The data obtained was assessed, and the percentage level of parental knowledge was categorized into three categories: good, sufficient, and poor. The level of parental knowledge regarding myofunctional therapy in Down syndrome was divided into two groups: those who had received information and those who had not. Results: The results of data analysis from 96 respondents were divided into two groups, namely the group that had received information with the results of the level of knowledge included in the good category (70.27%) and those who had never received information with the results of the level of knowledge included in the poor category (45.77%). Conclusion: The level of parental knowledge regarding myofunctional therapy in Down’s syndrome at the POTADS Foundation is in the good category for the group who received information and the poor category for the group who never received information about myofunctional therapyKEY WORDS: Down Syndrome, Knowledge, Myofunctional TherapyTingkat pengetahuan orang tua terhadap terapi myofungsional pada Down syndrome: studi cross-sectionalABSTRAK Pendahuluan: Down syndrome merupakan kelainan genetik yang berhubungan dengan penambahan kromosom 21 dan masih menjadi salah satu kelainan cacat lahir yang paling sering terjadi. Salah satu karakteristik fisik yang khas dan sering dijumpai adalah hipotonia otot termasuk otot orofasial dan otot lidah. Penanganan hipotonia otot harus diatasi dengan terapi myofungsional yang dilakukan secara rutin. Tujuan penelitian ini adalah untuk mengidentifikasi pengetahuan orang tua terhadap terapi myofungsional pada Down syndrome di Yayasan Persatuan Orang Tua Anak dengan Down Syndrome (POTADS). Metode: Jenis penelitian ini adalah dengan desain survei cross sectional. Sampel diperoleh dengan metode purposive sampling menghasilkan 96 sampel penelitian dari POTADS. Pengambilan data dilakukan dengan menggunakan kuesioner melalui perangkat google form. Data yang didapatkan dinilai dan persentase nilai pengetahuan orang tua akan dikategorikan dalam tiga kategori yaitu baik, cukup, dan kurang. Tingkat pengetahuan orang tua terhadap terapi myofungsional pada Down syndrome akan dikelompokkan menjadi dua yaitu orang tua yang pernah mendapat informasi dan belum pernah mendapat informasi. Hasil: Hasil analisis data dari 96 responden terbagi menjadi dua kelompok yaitu kelompok yang pernah mendapat informasi dengan hasil tingkat pengetahuan termasuk pada kategori baik (70,27%) dan yang belum pernah mendapat informasi dengan hasil tingkat pengetahuan termasuk pada kategori kurang (45,77%). Simpulan: Tingkat pengetahuan orang tua terhadap terapi myofungsional pada anak Down syndrome di Yayasan POTADS, berada pada kategori baik bagi kelompok yang pernah mendapatkan informasi dan kategori kurang bagi kelompok yang belum pernah mendapatkan informasi mengenai terapi myofungsional.KATA KUNCI: Sindrom Down, Pengetahuan, Terapi Myofungsional